2006
DOI: 10.1097/00000542-200605000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms Underlying the QT Interval–prolonging Effects of Sevoflurane and Its Interactions with Other QT-prolonging Drugs

Abstract: Prolonged ventricular repolarization observed with administration of sevoflurane results from inhibition of KvLQT1/minK and Kv4.3 cardiac K channels. Combining sevoflurane with class III antiarrhythmic drugs results in supra-additive effects on action potential duration. The results indicate that sevoflurane, when administered with this class of drug, could result in excessive delays in ventricular repolarization. The results suggest the need for further clinical studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 0 publications
3
31
0
1
Order By: Relevance
“…These differential effects of propofol on I Kr and I Ks are qualitatively similar to those of sevoflurane (Heath and Terrar, 1996;Kang et al, 2006, Kojima et al, 2015Shibata et al, 2004). Previous studies have demonstrated that propofol concomitantly blocks other ionic currents, especially L type Ca 2+ current (I Ca,L ) in ventricular myocytes (Yang et al, 1996), which results in minimal or no effect on ventricular action potential duration and QTc interval in experimental and clinical settings (Kojima et al, 2015;Puttick and Terrar, 1992;Staikou et al, 2014).…”
supporting
confidence: 54%
“…These differential effects of propofol on I Kr and I Ks are qualitatively similar to those of sevoflurane (Heath and Terrar, 1996;Kang et al, 2006, Kojima et al, 2015Shibata et al, 2004). Previous studies have demonstrated that propofol concomitantly blocks other ionic currents, especially L type Ca 2+ current (I Ca,L ) in ventricular myocytes (Yang et al, 1996), which results in minimal or no effect on ventricular action potential duration and QTc interval in experimental and clinical settings (Kojima et al, 2015;Puttick and Terrar, 1992;Staikou et al, 2014).…”
supporting
confidence: 54%
“…Another example is sevoflurane, which inhibits hERG current in Xenopus oocytes in a concentration-dependent manner (10-27% inhibition at 0.14-0.65 mmol/L) and prolongs the QTc interval in guinea pigs dose-dependently (Yamada et al, 2006). This hERG-blocking potential of sevoflurane, however, was not confirmed by other groups, who detected hardly an effect of sevoflurane (0.65 mmol/L) on isolated I Kr in guinea pig ventricular myocytes (Shibata et al, 2004) or an only marginal inhibition of hERG current at supratherapeutic concentrations (-17% at 3 mmol/L; Kang et al, 2006). Instead of an I Kr or hERG block, these two groups demonstrated an I Ks block by sevoflurane (IC 50 0.38 mmol/L) and halothane (IC 50 1.07 mmol/L) in guinea pig ventricular myocytes (Shibata et al, 2004) and in KvLQT1-minK expressing Chinese hamster ovary (CHO) cells (sevoflurane IC 50 1.3 mmol/L; Kang et al, 2006).…”
Section: Cardiac Delayed Rectifier Potassium Channels I Kr and I Ksmentioning
confidence: 79%
“…Moreover, propofol inhibits L-type calcium currents (ICa), even at clinical concentrations [4]. Blockage of ICa is known to attenuate the QT interval, prolonging the effects of many drugs [3]. However, our conclusion was probably overstated because this study did not include patients at risk of ventricular dysrhythmias.…”
Section: To the Editormentioning
confidence: 89%
“…Kang et al [3] demonstrated that sevoflurane did not block the hERG channel current (IKr), but rather inhibited the channel that carries IKs (potassium currents). IKr, rather than IKs, inhibition causes drug-induced torsades de pointes.…”
Section: To the Editormentioning
confidence: 99%